Effects of Age on the Pronunciation Accuracy of English as a Second Language among the learners in the Public Sector institutions of KPK: https://doi.org/10.5281/zenodo.17419122 - Zahid Sardar (Journal of Religion and Society, 2025)
This paper examines how age affects accuracy in the pronunciation of English by students studying in state-sponsored colleges of Khyber Pakhtunkhwa (KPK), Pakistan. The pronunciation is a very important yet difficult part of the second language acquisition, which is influenced by a complex interaction of biological, psychological and sociolinguistic factors. The study was carried out through the application of a mixed-methods research design, which was organized using 120 participants divided into three age groups secondary school students, undergraduate students, and adult students who took part in professional language improvement courses. A set of three instruments was used to collect the data controlled pronunciation tests, auditory discrimination tasks and structured questionnaires. The results indicate that there is a statistically significant correlation between the age of learning and the phonological attainment. Older learners showed a significant deficit in the acquisition of native-like speech sound and prosodic aspects, and slower progress and greater tenacity of L1 (Pashto) phonological interference were observed in younger learners. Nevertheless, the research also outlines the important mediating factors, such as the motivation of the learners, the frequency of exposure to L2, and the quality of the classroom instruction, which can be used to alleviate age-related limitations. The study offers strong empirical evidence in the Critical Period Hypothesis (CPH) in the distinct Pakistani socio-educational context. The conclusions highlight the importance of age-based pedagogical approach and curriculum development in order to improve learning about English pronunciation in multilingual, resource-deficient settings such as KPK. Keywords: Age Factor, Pronunciation Accuracy, Second Language Acquisition (SLA), Critical Period Hypothesis (CPH), Phonological Attainment, L1 Interference (or Mother Tongue Influence), Public Sector Education, Khyber, Pakhtunkhwa (KPK), Pakistani ESL Context, Language Pedagogy.